Autophagy in glaucoma pathogenesis: Therapeutic potential and future perspectives - Li, Min; Gao, Zhao-Lin; Zhang, Quan-Peng; Luo, Ai-Xiang; Xu, Wei-Ye; Duan, Tian-Qi; Wen, Xu-Peng; Zhang, Ru-Qi; Zeng, Ru; Huang, Ju-Fang (Frontiers in Cell and Developmental Biology, 2022)
Glaucoma is a common blinding eye disease characterized by progressive loss of retinal ganglion cells (RGCs) and their axons, progressive loss of visual field, and optic nerve atrophy. Autophagy plays a pivotal role in the pathophysiology of glaucoma and is closely related to its pathogenesis. Targeting autophagy and blocking the apoptosis of RGCs provides emerging guidance for the treatment of glaucoma. Here, we provide a systematic review of the mechanisms and targets of interventions related to autophagy in glaucoma and discuss the outlook of emerging ideas, techniques, and multidisciplinary combinations to provide a new basis for further research and the prevention of glaucomatous visual impairment.